PENGARUH STATE GOAL ORIENTATION TERHADAP PERFORMANCE DENGAN SELF-EFFICACY SEBAGAI VARIABEL PEMODERASI APLIKASI MATA KULIAH AKUNTANSI KEUANGAN LANJUTAN II - Biduri, Sarwenda (Equilibrium: Jurnal Ekonomi-Manajemen-Akuntansi, 2018)
This goal of this research is want to know the effect of state goal orientation (SLGO) to performance and self-efficacy of accounting student. The sample in this study are students who have taken 2nd advanced financial accounting course which amounted to 136 respondents. Sample of this research is students who have taken 2nd advanced financial accounting course. Sampling technique used in this research is purposive sampling. The analysis tool used is SPSS version 18.0, the analytical technique used is validity test, reliability test, classic assumption test, simple linear regression analisys, t-test, correlation coefficient, and determinant coefficient. The t-test results show that the effect of SLGO on self-efficacy has a significance value is 0.007 and 0.005. The significance value of state performance goal orientation (SPGO) to self-efficacy is 0.130 and 0.596. The significance value of self-efficacy on the performance of accounting students is 0.033 and 0.041. It can be concluded that SLGO has an influence on self-efficacy, but state performance goal orientation has no effect on self-efficacy, and self-efficacy has an influence on accounting student performance.